Oral immunization of mice with attenuated Salmonella typhimurium containing a recombinant plasmid which codes for production of a 31-kilodalton protein of Brucella abortus. - Stabel, T J (1990)
Salmonella typhimurium chi 4064, an attenuated delta cya delta crp mutant of S. typhimurium SR-11, was used as a carrier for the plasmid pBA31-R7. This plasmid codes for the expression of a 31-kilodalton (kDa) protein from Brucella abortus (BCSP31). Recombinant S. typhimurium chi 4064(pBA31-R7) expressed BCSP31 in vitro as shown by Western blot (immunoblot) analysis. The plasmid was stable in vitro and in vivo and did not affect the ability of the mutant to invade and colonize the small intestine, mesenteric lymph nodes, liver, or spleen of BALB/cByJ mice. Animals orally immunized with S. typhimurium chi 4064(pBA31-R7) developed serum and intestinal antibody responses to the B. abortus 31-kDa protein and to salmonella endotoxin as measured by enzyme-linked immunosorbent assay. Mice orally immunized with S. typhimurium chi 4064pBA31-R7 did not develop a delayed-type hypersensitivity following a footpad injection with recombinant BCSP31. Antigen-specific blastogenic data also support these in vivo results. All data indicate that this route of antigen delivery is effective for stimulating antibody-mediated immunity but that the B. abortus 31-kDa protein is a poor immunogen for inducing a cell-mediated immune response in BALB/cByJ mice.